Outcome in acute ischemic stroke patients with large-vessel occlusion and initial mild deficits - Kazmi, Jacob S.; O'Hara, Joseph; Gandomi, Amir; Wang, Jason J.; Sanmartin, Maria X.; Yang, Bo; Sanelli, Pina C.; Katz, Jeffrey M. (Frontiers in Stroke, 2024)
Background: Management of patients with initially mild acute ischemic stroke (AIS), defined by National Institutes of Health Stroke Scale (NIHSS) scores 0 to 5, remains ambiguous despite advances in stroke treatment. Early identification of patients likely to deteriorate is critical in preventing lasting disability.We investigated the frequency and early predictors of poor functional outcome in AIS patients with large vessel occlusion (LVO) and initial mild deficits. Methods: We performed a retrospective observational study of consecutive AIS patients admitted to a single comprehensive stroke center between 2018 and 2021. Inclusion criteria were AIS diagnosis, arrival NIHSS 0 to 5, imaging-confirmed LVO, and arrival within 24 hours from last known well.Primary outcome was change in discharge modified Rankin Score (∆mRS) from baseline as 0-1 (stable outcome) or >1 (poor outcome). Early neurological deterioration was defined as mean NIHSS increase of >1 in the first 24-hour period. Univariate and multivariable regression analyses were performed. Mean daily NIHSS was compared between groups using ANOVA.Results: Of 4,410 stroke admissions, 120 patients met study inclusion, with 71 (59.2%) patients ∆mRS 0-1 and 49 (40.8%) patients ∆mRS >1. Mean arrival NIHSS was similar between groups.However, mean first 24-hour NIHSS was significantly higher in poor versus stable outcome groups (2.13 vs. 0.95; p<0.001). Demographic-adjusted multivariable logistic regression revealed that higher mean first 24-hour NIHSS was the sole early predictor of poor outcome (odds ratio 1.65 [95% confidence interval 1.18-2.48]). The only association with early neurological deterioration was vertebral artery occlusion (odds ratio 0.35 [95% confidence interval 0.14-0.81]). Trending mean daily NIHSS revealed that patients with poor outcomes deteriorate within 24 hours, a significant difference from the stable group (p < 0.001).Poor outcome occurred in a significant proportion of LVO patients with initial mild deficits. The only association was early neurological deterioration. To prevent poor outcomes, rapid identification of any clinical deterioration should prompt consideration of thrombectomy.